Caring for you vs. caring for the planet : empathic concern and emotions associated with energy-saving preferences in Singapore - Sharma, Swati (2021)
The influence of financial and legislative factors on energy-saving decisions is well-established. However, consumers can also be (de-)motivated when they have to appreciate the consequences of their energy-saving behaviours on others – for instance, increasing the air-conditioner temperature could affect children’s thermal comfort. Here, we report that higher levels of empathic concern – a basic human disposition to experience warmth and concern for others – are associated with energy-saving behaviour. We carried out three experimental studies (Study 1: N = 174, Study 2: N = 171, Study 3: N = 175) involving realistic decision-making scenarios that required balancing energy use in a space with other occupants’ needs. Crucially, participants’ energy-saving behaviour was associated with their level of empathic concern when the energy-use decisions affected others (co-workers or family members), despite that behaviour also being influenced by monetary considerations or the need to ensure the comfort of others. Moreover, the effect was independent and principally, additive to the influence of pro-environmental attitudes. These results improve existing models of energy-saving behaviour by highlighting that, beyond financial and legislative motives, the capacity to consider and act on other’s welfare could drive energy-saving behaviour – even at the expense of the comfort of co-workers and family.